Links without Locations: Information Packaging and Non-Monotone Anaphora - Hendriks, Herman; Dekker, Paul (Proceedings of the Amsterdam Colloquium, 1995)
In his work in information packaging- i.e., the structuring of propositional content in function of the speaker's assumptions about the hearer's information state- Vallduví (1992, 1993, 1994) identifies the informational primitives focus, link and tai, which are adapted from the traditional focus/ground and topic/comment approaches, and argues that the exploitation of information states of hearers by the information-packaging strategies of speakers reveals that these states have at least the internal structure of a system of Heimian file cards: links, which correspond to what are traditionally known as topics, say where-on what file card - theforcal information goes, and tails indicate how it firs there. The present paper gives various reasons for not believing this and proposes to model information states as Kampian discourse representation structures, without locations. This requires and leads to a different perspective on the function of links. They signal non-monotone anaphora: their discourse referent Y is anaphoric to an antecedent discourse marker X such that X ⊄ Y. This idea will be shown to subsume 'non-identitiy' anaphora, contrastive stress, pronoun referent resolution, and restrictiveness of relatives and adjectives.